Pelaksanaan Metode Simulasi Bimbingan Ibadah Haji pada KBIH Nurzikrillah di Kota Padang - Darmisa, Cici; Jamna, Jamaris (JFACE: Journal of Family, Adult, and Early Childhood Education, 2019)
This research is motivated by the good learning outcomes of the KBIH pilgrimage of the pilgrimage to Nur Zikrillah Kota Padang, allegedly because the Hajj rituals are carried out using the simulation method. This study aims to see the implementation of the simulation method of Hajj guidance in KBIH Nurzikrillah Kota Padang. This type of research is quantitative descriptive. The population of the study was KBIH Nur Zikrillah pilgrimage worshipers in 2019 totaling 235 people. The sampling technique is simple random sampling. Samples were taken from 30% of the population, 70 people. The data collection technique used was a questionnaire, a data collection tool using a questionnaire that contained a list of statements. Data analysis techniques use percentages. The results showed that: (1) the preparation of the Hajj guidance simulation was carried out well, (2) the Hajj guidance simulation process was carried out well, (3) the closing of the Hajj guidance simulation was carried out well. Can be seen from most of the congregation always giving statements. Research suggestions are in carrying out simulations, simulations have been prepared in full, the simulation process is followed closely, and reflection activities are held at the end of the simulation.